Accuracy improved multi-stage ADI-PML algorithm for dispersive open region FDTD problems - Ramadan, O. (Inst Engineering Technology-Iet, 2008)
An unconditionally stable multi-stage alternating direction implicit perfectly matched layer (ADI-PML) algorithm is presented for modelling dispersive open region finite difference time domain (FDTD) applications. In the proposed algorithm, the updating procedure of the field equations from the nth to (n + 1)th time step is carried out in four stages with a time increment of Delta(t)/4. Numerical examples carried out in two dimensions show that the proposed algorithm presents significant improvement over the conventional ADI-PML algorithm for different Courant-Friedrichs-Lewy numbers and for different cell sizes per wavelength.
Keywords: Media